Investigating Iraqi EFL Learners' Awareness of Selected English Proverbs - Chassab Jabir, Azhar (Journal of College of Education, 2020)
Learning English as a foreign language does  not refer to the mastery of  the rules or merely the grammar of  English  . Rather , it refers to the full understanding of the semantic ( and syntactic ) concepts of that language , and employing this in real life situations . In this sense , the current research represents an attempt at investigating the Iraqi  EFL Learners’ recognition and  production of selected English proverbs . The study is divided into five sections (  an  introduction , three sections and a conclusion ) .  Evidence shows   that English proverbs represent a   very important component in learning English as a foreign language , and that Iraqi EFL learners face considerable  difficulties in understanding and employing them in real life situations .
Keywords: Key words : English Proverbs , Arabic Proverbs , Oxford English Dictionary of English Proverbs